Chapter 2 Educational bases of didactic AVT in FLE - TALAVAN, NOA (Taylor & Francis, 2024)
Chapter 2: This chapter aims at providing a general panorama of the educational bases that support the use of didactic AVT or DAT in language education. The chapter will first present the reader with the basic educational principles that are directly approached when introducing subtitling and revoicing -to include all AVT modalities- in the language classroom. Next, it will concentrate on the specific benefits of using AVT in different educational stages -ranging from primary education to university levels and bilingual education-. Sample lesson plans to be used in every stage will be provided, together with guidelines and comments for teachers. Then, we will discuss the relevance of AVT in the framework of new teaching modalities -which include blended learning and online teaching-. Finally, the closing remarks will underline the main implications of using AVT for educational purposes.